2022
DOI: 10.3389/fnhum.2022.945953
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the triangle completion test in the real-world and in virtual reality

Abstract: BackgroundThe triangle completion test has been used to assess egocentric wayfinding for decades, yet there is little information on its reliability. We developed a virtual reality (VR) based test and investigated whether either test of spatial navigation was reliable.ObjectiveTo examine test-retest reliability of the real-world and VR triangle completion tests. A secondary objective was to examine the usability of the VR based test.Materials and methodsThirty healthy adults aged 18–45 years were recruited to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Interestingly, no differences were found in TCT among the populations. It should be noted that although some studies exhibited differences in Angle among older adults in pBVL and Control groups ( 35 ), other studies have shown a poor reliability of this measure ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, no differences were found in TCT among the populations. It should be noted that although some studies exhibited differences in Angle among older adults in pBVL and Control groups ( 35 ), other studies have shown a poor reliability of this measure ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…The triangle completion task provides a straightforward way to investigate homing accuracy and precision and has therefore been used both for real-world, as well as virtual navigation experiments. While recent results indicate that translation of results between real-world and virtual versions of the task should be undertaken with caution [30], the triangle completion task continues to be a paradigm of choice for a broad range of spatial cognition studies, especially in the virtual realm.…”
Section: Triangle Completion In Virtual Realitymentioning
confidence: 99%
“…This display mode is usually thought to be less immersive than HMD driven VR [39][40][41][42][43] and there is general agreement that researchers should continue to strive for a greater degree of immersion in their virtual tasks. However, there is still ongoing discussion about the differences in immersion and ease of use of different forms of virtual reality systems, with several authors pointing out that different media come with their own biases and results cannot necessarily be assumed to transfer across media [40,43,44], let alone from VR to real-world applications by default [30].…”
Section: Performing Distributed Virtual Navigation Experimentsmentioning
confidence: 99%
“…The linear distance walked, linear end-point error (distance between where the participant stopped and the origin), and angle error (absolute value of the angular error with respect to the ideal rotation angle) are recorded. Recently, concerns about the reliability of the TCT have been raised by McLaren and colleagues ( 187 ) who found that the test–retest reliability for the distance walked was moderate but it was poor for end-point error and angle error.…”
Section: Vestibular Perception: Spatial Navigationmentioning
confidence: 99%